Natural increase, net replacement rate, output and population dynamic of Aceh cattle in Livestock Breeding and Forage Center of Indrapuri - Widyaningrum, R.; Budisatria, I. G. S.; Maharani, D. (Diponegoro University, 2021)
This study aimed to estimate natural increase (NI), net replacement rate (NRR), output, and population dynamics of Aceh cattle at Livestock Breeding and Forage Center in Indrapuri, Aceh province. Data of population structure, mortality, birth rate, the number of animals entering the herd, and the number of animals released from the herd during 2019were used for determining NIandNRR, and it isusedfor estimation of output. Population structure data (2015-2019) were used to estimate the population dynamics. The results showed that NI was 19.08% (medium category). The availability of replacement stock exceeded the need for replacement (140.08% for male and 73.33% for female); the NRR was 240.08% (male) and 173.33% (female). The output of Aceh cattle was 3.92% (culled male), 5.58% (culled female); the remaining replacement stocks were 5.49% (male) and 4.09% (female) of the total population. The population of Aceh cattle from 2020 to 2024 was expected to increase by 6.02% (65 heads) on average. In conclusion, that BPTU-HPT Indrapuri can be categorized as a beef cattle producing region, but still need efforts to increase natural increase by increasing birth rate minimum 32.77% and reducing mortality maximum 3.0%, in combination with better management systems.